A Modified Pulse and Design Framework to Halve the Complexity of OFDM Spectral Shaping Techniques - Giménez, Javier; Cortés-Arrabal, José Antonio; Martos-Naya, Eduardo; Cañete-Corripio, Francisco Javier; Díez-del-Río, Luis (IEEE, 2024)
Orthogonal frequency division multiplexing (OFDM) is a widespread modulation but suffers from high out-of-band emissions (OOBE). Spectral shaping strategies such as precoding, active interference cancellation (AIC) and time-domain methods are effective at reducing the OOBE but entail optimization procedures and real-time implementation costs which might be considerable. This letter proposes a modification of the conventional OFDM waveform aimed at reducing the cost associated to many of the state-of-theart spectral shaping techniques and sets a framework for future works that want to benefit from the same reduction. This approach may reduce both the number of coefficients involved in the optimization and the number of products of its implementation by up to 50%.
https://openpolicyfinder.jisc.ac.uk/id/publication/3426
Keywords: Multiplexación; Optimización matemática; OFDM; Symbols; Optimization; Complexity theory; Real-time systems; Receivers; Precoding; Cognitive radio; Out-of-band emission; Sidelobe suppression; Pulse shaping; Cancellation carriers